Serum and salivary obestatin concentrations in the diagnosis of polycystic ovary syndrome (Annals of Medical Research, 2021)
Aim: : To measure obestatin levels in the blood and saliva samples of normal-weight patients with polycystic ovary syndrome (PCOS) in comparison with normal-weight healthy controls, and to determine whether there were relationships between blood and/or salivary obestatin levels and other measured parameters.Materials and Methods: Fifteen healthy women and 15 patients with PCOS, all of which had normal weight, were included in the study. Participants’ age, height, weight, menstrual characteristics, hormone levels, body mass index, waist/hip ratio, and modified Ferriman-Gallwey (FG) scores were recorded. Obestatin levels were measured in both fasting blood and saliva samples. Homeostasis Model Assessment (HOMA-IR) was used to predict insulin resistance.Results: In the PCOS group, menstrual cycle duration and FG scores were significantly higher (P-value, 0.001, 0.001, respectively). The levels of luteinizing hormone, total testosterone and androstenedione were significantly higher in the PCOS group than in the control group (P-value, 0.001, 0.009, 0.004, respectively). In the PCOS group, blood obestatin level was 1265.2 ± 221.9 pg/ml, salivary obestatin level was 3095.33 ± 310.2 pg/ml; whereas the control group demonstrated lower levels of 939.66 ± 72.3 pg/ml and 2611.20 ± 217.1 pg/mL, respectively. However, no statistically significant difference was found between the PCOS and control groups when comparing obestatin levels in blood or saliva (P-value, 0.218, 0.369, respectively). No correlation was found between blood and salivary obestatin levels in either group. Finally, obestatin levels were not associated with any of the other measured parameters.Conclusion: Our results suggest that increased levels of obestatin, albeit in a small amount that would not be statistically significant in normal weight patients with PCOS, may have significant effects on weight control in these patients. In addition, our findings show that saliva sample can be used as an alternative to blood sample in the measurement of obestatin level in patients with PCOS.
Keywords: Ferriman-Gallwey; normal weight; obestatin; polycystic ovary syndrome; saliva